MUSE observations of a changing-look AGN – I. The reappearance of the broad emission lines. Issue 1 (27th March 2019) - Raimundo, S I; Vestergaard, M; Koay, J Y; Lawther, D; Casasola, V; Peterson, B M
ABSTRACT: Optical changing-look Active Galactic Nuclei (AGN) are a class of sources that change type within a short time-scale of years or decades. This change is characterized by the appearance or disappearance of broad emission lines, often associated with dramatic AGN continuum flux changes that are orders of magnitude larger than those expected from typical AGN variability. In this work we study for the first time the host galaxy of a changing-look AGN, Mrk 590, using high spatial resolution optical and near-infrared observations. We discover that after ∼10 yr absence, the optical broad emission lines of Mrk 590 have reappeared. The AGN optical continuum flux however is still ∼10 times lower than that observed during the most luminous state in the 1990s. The host galaxy shows a 4.5 kpc radius star-forming ring with knots of ionized and cold molecular gas emission. Extended ionized and warm molecular gas emission is detected in the nucleus, indicating that there is a reservoir of gas as close as 60 pc from the black hole. We observe a nuclear gas spiral between radii r ∼ 0.5 and 2 kpc, which has been suggested as a dynamical mechanism able to drive the necessary gas to fuel AGN. We also discover blue-shifted and high velocity dispersion [O iii ] emission out to a radius of 1 kpc, tracing a nuclear gas outflow. The gas dynamics in Mrk 590 suggest a complex balance between gas inflow and outflow in the nucleus of the galaxy.